Psilocybin mitigates behavioral despair and cognitive impairment in treatment-resistant depression model using wistar kyoto rats - Zitong Wang; Brett Robbins; Ryan Zhuang; Rebekah van Bruggen; Thaisa Sandini; Xin-Min Li; Yanbo Zhang (Scientific Reports)
Abstract Major depressive disorder (MDD) is a leading cause of disability that affects over 300 million people globally. Despite multiple antidepressant trials, approximately one-third of MDD patients remain symptomatic, progressing to treatment-resistant depression (TRD). This persistence possibly is due to the multifaceted etiology of TRD, encompassing biological, psychological, and environmental factors. Chronic stress, prevalent in modern life, significantly contributes to mental health disorders and complicates TRD treatment. This study investigated psilocybin as a potential TRD treatment using a diathesis-stress animal model. Twenty-two male Wistar-Kyoto (WKY) rats were divided into control and stress groups, with the stress group further subdivided to receive either sham treatment or psilocybin as early intervention. Behavioral assessments demonstrated a significant and sustained beneficial effect of psilocybin on behavioral despair and cognitive impairment. Biochemical analyses revealed psilocybin-induced increases in thyroid-stimulating hormone (TSH) levels without significant changes in the hypothalamic-pituitary-adrenal (HPA) axis. The ability of psilocybin to counter stress-induced TSH reductions suggested that TSH may serve as a proxy marker of therapeutic response, although its causal role in mood regulation remains unclear. Additionally, following psilocybin administration, changes in cannabinoid receptor type I (CB1R) suggest a potential modulation of psilocybin intervention on the component of the endocannabinoid system (ECS), though causal links remain unconfirmed without antagonist studies. These findings highlight the potential of psilocybin to treat TRD through the targeting of previously unexplored biological pathways.